Nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2023114326
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-12
AI Technical Summary
【0008】 このような構成によれば、正極活物質層の細孔が小さいにも関わらず、初期抵抗特性および保存特性に優れる非水電解質二次電池を提供することができる。
Smart Images

Figure 2025011910000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, nonaqueous electrolyte secondary batteries such as lithium ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.
[0003] A positive electrode used in a non-aqueous electrolyte secondary battery such as a lithium ion secondary battery generally has a configuration in which a positive electrode active material layer is provided on a positive electrode current collector. The positive electrode active material layer contains positive electrode active material particles, and the positive electrode active material layer has pores formed by gaps between the positive electrode active material particles (see, for example, Patent Documents 1 to 3). In order to improve the performance of a non-aqueous electrolyte secondary battery, a technique is known in which an additive (also called a "positive electrode film forming agent" or "positive electrode additive") that forms a coating on the positive electrode is contained in the non-aqueous electrolyte (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-069822 A [Patent Document 2] International Publication No. 2021 / 186949 [Patent Document 3] International Publication No. 2023 / 054308 Summary of the Invention [Problem to be solved by the invention]
[0005] Recently, the demand for BEVs has been rapidly increasing, and further improvement in the performance of secondary batteries for driving power sources of BEVs is desired. One method for improving the performance is to densify the positive electrode active material layer. As a result of intensive research by the present inventor, it has been found that there are the following problems when densifying the positive electrode active material layer. That is, when the positive electrode active material layer is densified, the pore diameter of the positive electrode active material layer becomes too small, and it becomes difficult for the positive electrode film forming agent to penetrate into the fine pores of the positive electrode active material layer. As a result, it becomes difficult to form a uniform film in the positive electrode active material layer, which leads to a decrease in the durability of the non-aqueous electrolyte secondary battery. Specifically, the capacity deterioration during storage of the non-aqueous electrolyte secondary battery becomes large. In addition, high initial resistance characteristics are required for secondary batteries used as vehicle driving power sources.
[0006] Therefore, an object of the present invention is to provide a nonaqueous electrolyte secondary battery that is excellent in initial resistance characteristics and storage characteristics despite the small pores in the positive electrode active material layer. [Means for solving the problem]
[0007] The non-aqueous electrolyte secondary battery disclosed herein contains a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode includes a positive electrode current collector, and a positive electrode active material layer supported on the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and a conductive material. The peak pore size of the positive electrode active material layer is 0.50 μm to 0.70 μm. The content of the conductive material in the positive electrode active material layer is 0.2 mass % to 1.0 mass %. 80 mass % or more of the conductive material is carbon nanotubes. The non-aqueous electrolyte contains a non-aqueous solvent, an electrolyte salt, and a positive electrode coating agent.
[0008] With this configuration, it is possible to provide a nonaqueous electrolyte secondary battery that is excellent in initial resistance characteristics and storage characteristics, despite the small pores in the positive electrode active material layer. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing a schematic internal structure of a lithium-ion secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic exploded view showing the configuration of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.
[0011] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between positive and negative electrodes. Furthermore, in this specification, the term "electric vehicle (BEV)" refers to a vehicle that has a motor operated by a secondary battery as a power source, but does not have an internal combustion engine such as a gasoline engine.
[0012] Hereinafter, the present invention will be described in detail using as an example a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case, but it is not intended that the present invention be limited to the embodiment described therein.
[0013] The lithium ion secondary battery 100 shown in FIG. 1 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 1 does not accurately represent the amount of the nonaqueous electrolyte 80.
[0014] 1 and 2, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62. The positive electrode active material layer-free portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer-free portion 52a and the negative electrode active material layer-free portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.
[0015] The positive electrode current collector 52 constituting the positive electrode sheet 50 may be a known positive electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). The positive electrode current collector 52 is preferably aluminum foil.
[0016] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.
[0017] The positive electrode active material layer 54 contains a positive electrode active material and a conductive material. As the positive electrode active material, a known positive electrode active material used in a lithium ion secondary battery may be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, or the like may be used. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like.
[0018] The lithium composite oxide is preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element, and specific examples thereof include lithium nickel-based composite oxides, lithium cobalt-based composite oxides, lithium manganese-based composite oxides, lithium nickel manganese-based composite oxides, lithium nickel cobalt manganese-based composite oxides, lithium nickel cobalt aluminum-based composite oxides, and lithium iron nickel manganese-based composite oxides.
[0019] In this specification, the term "lithium nickel cobalt manganese composite oxide" includes oxides containing Li, Ni, Co, Mn, and O as constituent elements, as well as oxides containing one or more additional elements other than those. Examples of such additional elements include transition metal elements and typical metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. The additional element may be a semimetal element such as B, C, Si, or P, or a nonmetal element such as S, F, Cl, Br, or I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.
[0020] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), and lithium manganese iron phosphate.
[0021] These positive electrode active materials may be used alone or in combination of two or more. As the positive electrode active material, lithium nickel cobalt manganese based composite oxide is particularly preferable because of its excellent properties such as initial resistance characteristics.
[0022] The positive electrode active material is particulate, and the average particle diameter (median diameter: D50) of the positive electrode active material is not particularly limited, but is, for example, 0.05 μm to 25 μm, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm. The average particle diameter (D50) of the positive electrode active material can be determined, for example, by a laser diffraction scattering method.
[0023] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is, for example, 80 mass% or more, preferably 87 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and most preferably 97 mass% or more.
[0024] In this embodiment, at least carbon nanotubes (CNTs) are used as the conductive material of the positive electrode active material layer 54, and the proportion of CNTs in the conductive material is 80 mass % or more. The CNTs are usually dispersed in the form of single particles and / or aggregates together with the positive electrode active material in the positive electrode active material layer 54. When the conductive material contains 80 mass % or more of CNTs, the initial resistance of the lithium ion secondary battery 100 can be reduced. In other words, the initial resistance characteristics of the lithium ion secondary battery can be improved.
[0025] The type of CNT used is not particularly limited, and for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), etc. can be used. These can be used alone or in combination of two or more. As the CNT, MWCNT is preferable. The CNT may be manufactured by an arc discharge method, a laser ablation method, a chemical vapor deposition method, etc.
[0026] The average length of the CNTs is not particularly limited. If the average length of the CNTs is too long, the CNTs may aggregate and the dispersibility may decrease, and the effect of distributing the positive electrode coating agent uniformly in the positive electrode active material layer 54 may decrease. Therefore, the average length of the CNTs is preferably 10 μm or less, more preferably 5.0 μm or less, even more preferably 3.0 μm or less, and most preferably 1.0 μm or less. On the other hand, if the average length of the CNTs is too short, the number of CNTs per unit weight may be too small, and it may be difficult to form a conductive path between the positive electrode active materials. Therefore, the average length of the CNTs is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more.
[0027] The average diameter of the CNT is not particularly limited. If the average diameter of the CNT is too large, the number of CNTs per unit mass becomes too small, and it may be difficult to form a conductive path between the positive electrode active materials. Therefore, the average diameter of the CNT is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. On the other hand, if the average diameter of the CNT is too small, the hollow diameter of the CNT becomes too small, and the effect of improving the impregnation of the non-aqueous electrolyte 80 by the capillary phenomenon may decrease. Therefore, the average diameter of the CNT is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 8 nm or more.
[0028] It is particularly preferable that the average length of the CNTs is 0.3 μm to 1.0 μm and the average diameter of the CNTs is 8 nm to 30 nm.
[0029] The average length and average diameter of CNTs can be obtained, for example, by taking an electron microscope photograph of CNTs and averaging the lengths and diameters of 100 or more CNTs. Specifically, for example, a CNT dispersion is diluted and then dried to prepare a measurement sample. This sample is observed with a scanning electron microscope (SEM) to obtain the lengths and diameters of 100 or more CNTs and calculate the average value. At this time, if the CNTs are re-aggregated, the length and diameter are obtained for the bundle of aggregated CNTs.
[0030] Examples of conductive materials other than CNT include carbon materials (e.g., carbon black such as acetylene black (AB), graphite, etc.). Among these, carbon black is preferred, and acetylene black is particularly preferred.
[0031] From the viewpoint of particularly high initial resistance characteristics of the lithium ion secondary battery 100, the proportion of CNTs in the conductive material is preferably 90 mass % or more, and more preferably 100 mass % (ie, the conductive material is composed only of CNTs).
[0032] The content of the conductive material in the positive electrode active material layer 54 is 0.2% by mass to 1.0% by mass. The significance of this will be described later. The content of the conductive material in the positive electrode active material layer 54 is preferably 0.4% by mass to 1.0% by mass. In this case, the lithium ion secondary battery 100 is one in which an increase in resistance during long-term storage is highly suppressed.
[0033] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a binder, a carbon nanotube dispersant (CNT dispersant), etc. As the binder, for example, polyvinylidene fluoride (PVdF) or the like can be used.
[0034] Examples of CNT dispersants that can be used include surfactant-type dispersants (also called low molecular weight dispersants), polymer-type dispersants, and inorganic-type dispersants. The CNT dispersant may be anionic, cationic, amphoteric, or nonionic. Thus, the CNT dispersant may have at least one functional group selected from the group consisting of anionic groups, cationic groups, and nonionic groups in its molecular structure. The surfactant refers to an amphiphilic substance having a chemical structure in which a hydrophilic portion and a lipophilic portion are bonded together by a covalent bond in the molecular structure.
[0035] Specific examples of CNT dispersants include polycondensation aromatic surfactants such as sodium salt of naphthalenesulfonic acid formalin condensate, ammonium salt of naphthalenesulfonic acid formalin condensate, and sodium salt of methylnaphthalenesulfonic acid formalin condensate; polycarboxylic acids and their salts, such as polyacrylic acid and its salts, polymethacrylic acid and its salts; triazine derivative dispersants (preferably containing a carbazolyl group or a benzimidazolyl group); polyvinylpyrrolidone (PVP); polymers having polynuclear aromatics such as pyrene and anthracene in the side chain; polynuclear aromatic ammonium derivatives such as pyrene ammonium derivatives (e.g., compounds in which an ammonium bromide group is introduced into pyrene) and anthracene ammonium derivatives; and the like. These CNT dispersants can be used alone or in combination of two or more. As the CNT dispersant, those containing polynuclear aromatics are preferable. Specifically, as the CNT dispersant, polymers having polynuclear aromatics in the side chain and polynuclear aromatic ammonium derivatives are preferable.
[0036] The content of trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably from 1 to 15% by mass, and more preferably from 2 to 12% by mass. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably from 0.1 to 10% by mass, more preferably from 0.2 to 5% by mass, and even more preferably from 0.3 to 2% by mass.
[0037] The amount of the CNT dispersant may be appropriately determined depending on the type of CNT and CNT dispersant. Here, if the ratio of the CNT dispersant is too small, dispersibility may be insufficient. On the other hand, if the ratio of the CNT dispersant is too large, the CNT dispersant may adhere excessively to the CNT surface, causing an increase in resistance. When the CNT is SWCNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 400 parts by mass, preferably 20 parts by mass to 200 parts by mass, relative to 100 parts by mass of CNT. When the CNT is MWNT, the amount of the CNT dispersant used is, for example, 1 part by mass to 100 parts by mass, preferably 4 parts by mass to 40 parts by mass, relative to 100 parts by mass of CNT.
[0038] The positive electrode active material layer 54 has pores that are interconnected spaces between the positive electrode active material particles. In this embodiment, the peak pore size of the positive electrode active material layer 54 is 0.50 μm to 0.70 μm. In this embodiment, the pores of the positive electrode active material layer 54 are small. However, by causing the positive electrode active material layer 54 to contain 0.2 mass % to 1.0 mass % of a conductive material that is 80 mass % or more of CNT, the storage characteristics of the lithium ion secondary battery 100 can be improved.
[0039] By making the content of the conductive material 0.2 mass % or more and making 80 mass % or more of the conductive material CNT, the impregnation of the nonaqueous electrolyte 80 into the positive electrode active material layer 54 is improved by the capillary phenomenon caused by the CNT in the pores of the positive electrode active material layer 54. As a result, the positive electrode film forming agent can be supplied to the fine details of the pores of the positive electrode active material layer 54 together with the nonaqueous electrolyte 80. As a result, the positive electrode film forming agent can be uniformly distributed in the positive electrode active material layer 54, and when the lithium ion secondary battery 100 is initially charged, a film can be uniformly formed in the positive electrode active material layer 54. This can improve the storage characteristics of the lithium ion secondary battery 100. On the other hand, if the content of the conductive material is too high, i.e., if it exceeds 1.0 mass %, the nonaqueous electrolyte 80 becomes difficult to flow through the pores due to the excess conductive material. Therefore, by making the content of the conductive material 1.0 mass % or less, the positive electrode film forming agent can be uniformly distributed within the positive electrode active material layer 54, and the effect of improving the storage characteristics of the lithium ion secondary battery 100 described above can be highly obtained.
[0040] Furthermore, since the conductive material contains 80% by mass or more of CNT, a good conductive path is formed in the positive electrode active material layer 54, which reduces the initial resistance of the lithium ion secondary battery 100 and thereby improves the initial resistance characteristics.
[0041] The peak pore diameter of the positive electrode active material layer 54 can be measured according to mercury intrusion porosimetry. Specifically, the peak pore diameter of the positive electrode active material layer 54 can be measured using a mercury porosimeter according to a known method.
[0042] The pores of the positive electrode active material layer 54 are formed by the gaps between the positive electrode active material particles. Therefore, the peak pore diameter of the positive electrode active material layer 54 can be adjusted by controlling the porosity of the positive electrode active material layer 54. The smaller the porosity of the positive electrode active material layer 54, the smaller the peak pore diameter of the positive electrode active material layer 54 tends to be. The porosity of the positive electrode active material layer 54 can be adjusted by changing the pressing conditions of the positive electrode active material layer 54 when producing the positive electrode 50, controlling the particle diameter of the positive electrode active material particles, etc. Alternatively, the pore diameter can be reduced by disposing a conductive material in the gaps between the positive electrode active material particles. Therefore, the peak pore diameter of the positive electrode active material layer 54 can also be controlled by the amount of conductive material used.
[0043] The porosity of the positive electrode active material layer 54 is preferably 15 volume % to 40 volume %, more preferably 15 volume % to 30 volume %, and further preferably 15 volume % to 25 volume %. The porosity of the positive electrode active material layer 54 can be measured according to mercury intrusion porosimeter. Specifically, the porosity of the positive electrode active material layer 54 can be measured using a mercury porosimeter according to a known method.
[0044] The thickness of the positive electrode active material layer 54 is not particularly limited, but is, for example, not less than 10 μm and not more than 400 μm, and preferably not less than 20 μm and not more than 300 μm.
[0045] The density of the positive electrode active material layer 54 is not particularly limited and is, for example, 2.00 g / cm 3 ~4.00g / cm 3 From the viewpoint of high volumetric energy density, the density of the positive electrode active material layer 54 is preferably 3.00 g / cm 3 ~4.00g / cm 3 and more preferably 3.40 g / cm 3 ~4.00g / cm 3 and more preferably 3.50 g / cm 3 ~4.00g / cm 3 and particularly preferably 3.60 g / cm 3 ~4.00g / cm 3 It is.
[0046] The positive electrode sheet 50 may contain an insulating layer (not shown) at the boundary between the positive electrode active material layer non-forming portion 52a and the positive electrode active material layer 54. The insulating layer contains, for example, ceramic particles.
[0047] The negative electrode current collector 62 constituting the negative electrode sheet 60 may be a known negative electrode current collector used in lithium ion secondary batteries, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.
[0048] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 6 μm or more and 20 μm or less.
[0049] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, soft carbon, etc. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.
[0050] The average particle diameter (median diameter: D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm. The average particle diameter (D50) of the negative electrode active material can be determined, for example, by a laser diffraction scattering method.
[0051] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.
[0052] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.
[0053] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 400 μm, and preferably not less than 20 μm and not more than 300 μm.
[0054] The separator 70 may be a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. Such a porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which a PP layer is laminated on both sides of a PE layer). A heat-resistant layer (HRL) containing ceramic particles or the like may be provided on the surface of the separator 70.
[0055] The thickness of the separator 70 is not particularly limited, but is, for example, 5 μm to 50 μm, and preferably 10 μm to 30 μm. The air permeability of the separator 70 obtained by the Gurley test method is not particularly limited, but is preferably 350 sec / 100 cc or less.
[0056] The non-aqueous electrolyte 80 contains a non-aqueous solvent, an electrolyte salt (in other words, a supporting salt), and a positive electrode film-forming agent.
[0057] As the non-aqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, lactones, etc., which are used in the electrolyte of a general lithium ion secondary battery, can be used without any particular limitation. Among them, carbonates and esters are preferable, and specific examples thereof include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), methyl acetate, methyl propionate, etc. Such non-aqueous solvents can be used alone or in appropriate combination of two or more. The non-aqueous solvent contains, for example, only carbonates. The non-aqueous solvent contains, for example, only carbonates and esters.
[0058] As the electrolyte salt, for example, a lithium salt such as LiPF6, LiBF4, or lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be suitably used. The concentration of the electrolyte salt in the non-aqueous electrolyte 80 is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0059] The positive electrode film-forming agent is a component that forms a film on the positive electrode active material layer 54 (particularly the surface of the positive electrode active material particles) when the lithium ion secondary battery 100 is initially charged, and is also called a positive electrode additive. As the positive electrode film-forming agent, at least one selected from the group consisting of lithium difluorophosphate (LiPO2F2) and lithium fluorosulfate (LiSO3F) can be suitably used. By using these, the storage characteristics of the lithium ion secondary battery 100 can be particularly improved.
[0060] The concentration of the positive electrode film forming agent in the non-aqueous electrolyte 80 is not particularly limited and is, for example, 0.05 mass % to 2.0 mass %, preferably 0.1 mass % to 1.8 mass %, and more preferably 0.3 mass % to 1.5 mass %.
[0061] The nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as a negative electrode film-forming agent, such as vinylene carbonate (VC) or an oxalate complex; a gas generating agent, such as biphenyl (BP) or cyclohexylbenzene (CHB); a thickener, etc., as long as the effects of the present invention are not significantly impaired.
[0062] In the lithium ion secondary battery 100, even though the pores in the positive electrode active material layer are small, capacity degradation during long-term storage is suppressed. In addition, in the lithium ion secondary battery 100, an increase in resistance during long-term storage is also effectively suppressed. Thus, the lithium ion secondary battery 100 has excellent storage characteristics. Furthermore, the lithium ion secondary battery 100 also has excellent input characteristics. Furthermore, the reaction distribution in the positive electrode 50 is easily uniform, which makes it difficult for lithium to deposit on the surface of the negative electrode 60, and therefore makes it difficult for capacity degradation to occur.
[0063] The lithium ion secondary battery 100 can be used for various applications. Suitable applications include a driving power source mounted on vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs). The lithium ion secondary battery 100 can also be used as a storage battery for small power storage devices and the like. A particularly suitable application of the lithium ion secondary battery 100 is as a driving power source for BEVs. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of batteries are typically connected in series and / or parallel.
[0064] The above describes, as an example, a rectangular lithium ion secondary battery 100 equipped with a flat wound electrode assembly 20. However, the lithium ion secondary battery can also be configured as a lithium ion secondary battery equipped with a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The lithium ion secondary battery can also be configured as a cylindrical lithium ion secondary battery, a laminated case type lithium ion secondary battery, etc.
[0065] The secondary battery according to this embodiment can be constructed as a non-aqueous electrolyte secondary battery other than a lithium ion secondary battery according to a known method.
[0066] Examples of the present invention will be described in detail below, but it is not intended that the present invention be limited to those shown in these examples.
[0067] [Examples 1 to 3 and Comparative Examples 1 to 8] LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2, a conductive material, and PVdF as a binder were mixed in a mass ratio of active material:conductive material:PVdF=99.5-x:x:0.5. Note that MWCNT (average diameter 13 nm, average length 0.5 μm) and acetylene black were used as the conductive material. MWCNT was used in the form of a dispersion liquid, and the dispersion liquid contained pyrene ammonium salt as a CNT dispersant. x1 in Table 1 is the mass ratio of MWCNT, x2 in Table 2 is the mass ratio of AB, and the sum of x1 and x2 is the mass ratio x of the conductive material.
[0068] A suitable amount of N-methyl-2-pyrrolidone was added to the obtained mixture to prepare a positive electrode slurry. The positive electrode slurry was applied to both sides of an aluminum foil having a thickness of 13 μm as a positive electrode current collector. At this time, a positive electrode slurry uncoated portion was provided on the aluminum foil as a lead connection portion. The amount of the positive electrode slurry applied was adjusted so that the basis weight of the positive electrode active material layer formed was 45 mg / cm2 in total on both sides. 2 It was adjusted so that
[0069] The applied slurry was dried to form a positive electrode active material layer. The obtained sheet was pressed with a roller to densify the positive electrode active material layer and adjust the porosity of the positive electrode active material layer to 21% by volume. The porosity was measured with a commercially available mercury porosimeter. The sheet was cut to a predetermined size to obtain a positive electrode in which a positive electrode active material layer was formed on both sides of the positive electrode current collector.
[0070] Graphite as a carbon-based negative electrode active material, sodium salt of carboxymethylcellulose (CMC-Na), and a dispersion of styrene butadiene rubber (SBR) were mixed in a solid mass ratio of graphite:CMC-Na:CMC=98:1:1. An appropriate amount of ion-exchanged water was further added to prepare a negative electrode slurry. The negative electrode slurry was applied to both sides of a copper foil with a thickness of 8 μm as a negative electrode current collector. At this time, a negative electrode slurry uncoated portion was provided on the copper foil as a lead connection portion.
[0071] The applied paste was dried to form a negative electrode active material layer. The obtained sheet was pressed with a roller and then cut to a predetermined size to obtain a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector. The packing density of the negative electrode active material layer was 1.50 g / cm. 3 It was.
[0072] A lead was attached to each of the positive and negative electrodes prepared above. A single-layer polypropylene separator was prepared. The positive and negative electrodes were alternately stacked one by one with the separators interposed therebetween to prepare a laminated electrode body.
[0073] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 was prepared. Vinylene carbonate was dissolved in this mixed solvent at a concentration of 1 mass%, lithium bis(oxalate)borate was dissolved in a concentration of 0.8 mass%, lithium fluorosulfate as a positive electrode film forming agent was dissolved in a concentration of 1.5 mass%, and LiPF6 as a supporting salt was dissolved in a concentration of 1.15 mol / L. However, in Comparative Example 8, the positive electrode film forming agent was not added. In this manner, a nonaqueous electrolyte was obtained.
[0074] The laminated electrode body and the non-aqueous electrolyte were placed in a square battery case and sealed to obtain a square lithium ion secondary battery for evaluation. The amount of non-aqueous electrolyte injected was 2.05 g / Ah.
[0075] <Peak pore size measurement> Using a commercially available mercury porosimeter (Autopore V9620 manufactured by Micromeritics), the peak pore diameter (μm) of the positive electrode active material layer of the above-prepared positive electrode was determined. The results are shown in Table 1.
[0076] <PC Impregnation Rate Evaluation> 3 μL of propylene carbonate (PC) solvent was dropped onto the positive electrode active material layer of the above-prepared positive electrode using a micropipette. Visually, the time (seconds) from the dropping until all of the PC solvent was absorbed into the positive electrode active material layer was measured. This measurement was performed 20 times, and the average value was adopted as the PC impregnation time. The results are shown in Table 1. Note that the shorter this PC impregnation time, the faster the PC impregnation rate, which means that the non-aqueous electrolyte is more likely to impregnate the positive electrode active material layer.
[0077] <Initial Resistance Characteristic Evaluation - Input Resistance Measurement> Each lithium-ion secondary battery for evaluation was adjusted to SOC 50% by constant current constant voltage (CC-CV) charging and then placed in an environment at 25°C. Charging was performed at a current value of 4C for 10 seconds, and the voltage increase amount ΔV at this time was obtained. Using this voltage increase amount ΔV and the current value, the input resistance value (initial input resistance) of each evaluation secondary battery was calculated. The results are shown in Table 1.
[0078] <Storage Characteristic Evaluation> Each lithium-ion secondary battery for evaluation was placed in an environment at 25°C and charged to 4.25V by CC-CV charging (0.01C cut-off) to adjust to SOC 100%. Then, CC-CV discharge (0.01C cut-off) was performed to 3V at a current value of 1 / 3C. The discharge capacity at this time was measured and used as the initial capacity.
[0079] Next, each lithium-ion secondary battery for evaluation was adjusted to SOC 95% and stored in a thermostat at 60°C for 45 days. Then, the discharge capacity was measured in the same manner as the initial capacity. The capacity retention rate (%) was calculated from (Discharge capacity after storage / Initial capacity) × 100. The results are shown in Table 1.
[0080] The input resistance value of each evaluation lithium ion secondary battery after storage was measured in the same manner as above. The resistance increase rate was calculated as (input resistance after storage / initial input resistance). The results are shown in Table 1. In Comparative Example 7, since the initial input resistance was high, the storage characteristics were not evaluated.
[0081] <Measurement of remaining concentration of positive electrode film forming agent> Each evaluation lithium-ion secondary battery was placed in a 25°C environment and charged to 4.25V by CC-CV charging, and adjusted to SOC100%. Then, CC-CV discharge was performed to 3V at a current value of 1 / 3C. Then, each evaluation lithium-ion secondary battery was disassembled and the non-aqueous electrolyte was collected. The remaining concentration of the positive electrode film-forming agent in the non-aqueous electrolyte was measured using an Oxford Instruments benchtop NMR spectrometer "X-Pulse" (with autosampler "X-Auto"). The results are shown in Table 1.
[0082] [Table 1]
[0083] The results of Comparative Examples 2 to 6 show that the larger the peak pore diameter of the positive electrode active material layer, the shorter the PC impregnation time, i.e., the higher the impregnation of the non-aqueous electrolyte. Here, Comparative Examples 2 to 5 are examples in which only AB is used as the conductive material. In Comparative Examples 2 to 5, it is found that the smaller the amount of AB, the larger the peak pore diameter, the higher the impregnation of the non-aqueous electrolyte, and the more the positive electrode film forming agent is consumed for film formation. In addition, it is found that the smaller the amount of AB, the worse both the input characteristics and storage characteristics are.
[0084] On the other hand, Examples 1 to 3 and Comparative Example 1 are examples in which only CNT is used as the conductive material. Comparison with Comparative Examples 2 to 6 shows that when CNT is used as the conductive material, a tendency different from that when AB is used is obtained. Specifically, when the CNT content is 0.2 mass% to 1.0 mass%, it is found that the residual concentration of the positive electrode film forming agent is specifically low, the input resistance is low, and the storage characteristics are high. This is considered to be because the CNT allows the positive electrode film forming agent to penetrate into the fine pores of the positive electrode active material layer, and a uniform film can be formed in the positive electrode active material layer.
[0085] Furthermore, a comparison of Comparative Example 7 with Examples 1 to 3 reveals that only when the proportion of CNTs in the conductive material is high, it is possible to reduce the input resistance and improve the storage characteristics.
[0086] From the above, it is seen that the nonaqueous electrolyte secondary battery disclosed herein can provide a nonaqueous electrolyte secondary battery that is excellent in input characteristics and storage characteristics, despite the small pores in the positive electrode active material layer.
[0087] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.
[0088] That is, the nonaqueous electrolyte secondary battery disclosed herein has the following features [1] to [6]. [1] Positive electrode, a negative electrode, and Nonaqueous electrolyte A non-aqueous electrolyte secondary battery comprising: the positive electrode comprises a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and a conductive material, The peak pore diameter of the positive electrode active material layer is 0.50 μm to 0.70 μm, The content of the conductive material in the positive electrode active material layer is 0.2% by mass to 1.0% by mass, 80% by mass or more of the conductive material is carbon nanotubes, The non-aqueous electrolyte contains a non-aqueous solvent, an electrolyte salt, and a positive electrode film forming agent. Nonaqueous electrolyte secondary battery. [2] The nonaqueous electrolyte secondary battery according to item [1], wherein the conductive material is composed only of the carbon nanotubes. [3] The nonaqueous electrolyte secondary battery according to item [1] or [2], wherein the positive electrode film forming agent is at least one selected from the group consisting of lithium difluorophosphate and lithium fluorosulfate. [4] The nonaqueous electrolyte secondary battery according to any one of items [1] to [3], wherein the content of the conductive material in the positive electrode active material layer is 0.4% by mass to 1.0% by mass. [5] The nonaqueous electrolyte secondary battery according to any one of items [1] to [4], wherein the carbon nanotubes have an average length of 0.3 μm to 1.0 μm and an average diameter of 8 nm to 30 nm. [6] The nonaqueous electrolyte secondary battery according to any one of items [1] to [5], which is used as a vehicle driving power source for an electric vehicle. [Explanation of symbols]
[0089] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Portion where positive electrode active material layer is not formed 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Part where negative electrode active material layer is not formed 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Non-aqueous electrolytes 100 Lithium-ion secondary battery
Claims
1. positive electrode, a negative electrode, and Nonaqueous electrolyte A non-aqueous electrolyte secondary battery comprising: the positive electrode comprises a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material and a conductive material, The peak pore diameter of the positive electrode active material layer is 0.50 μm to 0.70 μm, The content of the conductive material in the positive electrode active material layer is 0.2% by mass to 1.0% by mass, 80% by mass or more of the conductive material is carbon nanotubes, The non-aqueous electrolyte contains a non-aqueous solvent, an electrolyte salt, and a positive electrode film forming agent. Nonaqueous electrolyte secondary battery.
2. 2. The nonaqueous electrolyte secondary battery in accordance with claim 1, wherein the conductive material consists essentially of the carbon nanotubes.
3. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the positive electrode film-forming agent is at least one selected from the group consisting of lithium difluorophosphate and lithium fluorosulfate.
4. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of the conductive material in the positive electrode active material layer is 0.4% by mass to 1.0% by mass.
5. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the carbon nanotubes have an average length of 0.3 μm to 1.0 μm and an average diameter of 8 nm to 30 nm.
6. 2. The nonaqueous electrolyte secondary battery according to claim 1, which is used as a vehicle driving power source for an electric vehicle.
Citation Information
Patent Citations
Positive electrode for secondary battery and secondary battery containing the same
JP2018535520A
Electrode for lithium-ion secondary battery, and lithium-ion secondary battery using said electrode
WO2013179924A1
Lithium ion secondary cell
WO2017217408A1
Positive electrode for nonaqueous electrolyte secondary batteries and nonaqueous electrolyte secondary battery
WO2021124970A1
Non-aqueous electrolyte secondary battery
WO2023032499A1